2019
DOI: 10.1002/cssc.201901661
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Aluminum Catalysts for the Chemical Conversion of CO2 into Cyclic Carbonates at Room Temperature and Atmospheric CO2 Pressure

Abstract: A series of dimeric aluminum compounds [Al(OCMe2CH2N(R)CH2X)]2 [X=pyridin‐2‐yl, R=H (PyrH); X= pyridin‐2‐yl, R=Me (PyrMe); X=furan‐2‐yl, R=H (FurH); X= furan‐2‐yl, R=Me (FurMe); X=thiophen‐2‐yl, R=H (ThioH); X= thiophen‐2‐yl, R=Me (ThioMe)] containing heterocyclic pendant group attached to the nitrogen catalyze the coupling of CO2 with epoxides under ambient conditions. In a comparison of their catalytic activities with those of aluminum complexes without pendant groups at N [X=H, R=H (HH); X=H, R=Me (HMe)] or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 32 publications
(56 reference statements)
2
28
0
Order By: Relevance
“…CO 2 is an ideal C1 resource as it is rich, renewable, and nontoxic. However, its stable thermodynamic properties greatly limit its application. , Cycloaddition of CO 2 and epoxides is a 100% atom-economic reaction which forms cyclic carbonates that have found extensive application as battery electrolyte, pharmaceutical/fine chemical intermediates, polymer and engineering plastic syntheses, aprotic polar solvents, etc. Reactions of CO 2 and epoxides may also produce polycarbonates, which may be used as food packagings, adhesives, and optical media . A number of catalysts have been developed to catalyze the cycloaddition reaction, including transition metal (e.g., Cr, , Mn, , Fe, Co, and Zn), main group metal (e.g., Al, Mg, and Ca), rare-earth (RE) metal, and organocatalysts. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CO 2 is an ideal C1 resource as it is rich, renewable, and nontoxic. However, its stable thermodynamic properties greatly limit its application. , Cycloaddition of CO 2 and epoxides is a 100% atom-economic reaction which forms cyclic carbonates that have found extensive application as battery electrolyte, pharmaceutical/fine chemical intermediates, polymer and engineering plastic syntheses, aprotic polar solvents, etc. Reactions of CO 2 and epoxides may also produce polycarbonates, which may be used as food packagings, adhesives, and optical media . A number of catalysts have been developed to catalyze the cycloaddition reaction, including transition metal (e.g., Cr, , Mn, , Fe, Co, and Zn), main group metal (e.g., Al, Mg, and Ca), rare-earth (RE) metal, and organocatalysts. …”
Section: Introductionmentioning
confidence: 99%
“…Organocatalysts include pincer-type compounds and phosphorus ylide-CO 2 adducts, which catalyzed cycloaddition of 1,2-disubstituted epoxides at 80 and 100 °C, respectively, in the presence of 1 bar CO 2 . , Other examples include the Cr­(salophen) complex and RE–Zn heterobimetallic complexes, which required both high temperature and pressure for disubstituted epoxides. ,, Among all examples discussed above, reactions of disubstituted epoxides under 1 bar CO 2 are mainly limited to 1,1-disubstituted epoxides and CHO, ,, whereas other disubstituted epoxides required elevated pressure. The only exceptions include the carboxylic acid-functionalized benzimidazolium salt reported by Dai et al and aluminum complexes chelated by ethanolateamine reported by Kim et al, which catalyzed cycloaddition of up to eight 1,2-disubstituted epoxides with 1 bar CO 2 at 80 and 75 °C, respectively. Therefore, development of a catalyst efficient for transformation of disubstituted epoxides under ambient conditions is highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…The bands occurring in the wavenumber range 400–415 cm −l are assigned due to stretching vibration of ν(M–O). [ 29–32 ]…”
Section: Resultsmentioning
confidence: 99%
“…The bands occurring in the wavenumber range 400-415 cm Àl are assigned due to stretching vibration of ν(M-O). [29][30][31][32] It is reasonable to assume that the prepared ligand considered as a neutral bidentate ligand coordinated through the two carbonyl and epoxy oxygen atoms to the transition metal cations.…”
Section: Ft-ir Spectral Studiesmentioning
confidence: 99%
“…The conversion reaction of CO 2 and epoxides to cyclic organic carbonates has a 100% atom economy, and the cyclic carbonates are important intermediates for polymers [ 2 , 3 ], agrochemicals, pharmaceuticals [ 4 ], electrolytes in lithium-ion batteries [ 5 ], polar aprotic solvents [ 6 , 7 ], and temporal protecting groups for cis-diols [ 8 ]. Owing to the usefulness of cyclic carbonate compounds, various catalysts have been developed for the reaction between CO 2 and epoxides [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%